Formulation and Characterization of Curcumin-Loaded Aquasomes for Topical Fungal Treatment - Patel, Mrigendra Kumar; Shah, Sunil; Dubey, B. K.; Basedia, Deepak Kumar; Jain, Prabhat Kumar (Asian Journal of Pharmaceutical Research and Development, 2025)
The topical treatment of fungal infections remains a significant challenge due to the limited bioavailability of many therapeutic agents when applied on the skin. Curcumin, a naturally occurring polyphenolic compound derived from Curcuma longa, has demonstrated notable antifungal, anti-inflammatory, and antioxidant properties, making it an ideal candidate for the treatment of skin infections. However, its hydrophobic nature and poor solubility in water limit its therapeutic efficacy. To address these limitations, this study aimed to develop and evaluate curcumin-loaded aquasomes as a novel drug delivery system for topical fungal treatment. Aquasomes are a type of nanoparticulate carrier composed of a stabilizer, such as gelatin, and a surfactant, such as Tween 80, which are cross-linked with glutaraldehyde to form a stable, nanostructured system that encapsulates the drug. The curcumin-loaded aquasomes were prepared using the solvent evaporation method, followed by characterization of vesicle size, surface charge, entrapment efficiency, in vitro drug release, and release kinetics. The results showed that the optimized formulation (F3) had a vesicle size of 125.65 nm, a surface charge of 36.85 mV, and an entrapment efficiency of 82.23%. The in vitro release studies revealed a sustained release of curcumin over 12 hours, with 98.12% of the drug being released. The release data followed Korsmeyer-Peppas kinetics, indicating a diffusion-controlled release mechanism. The TEM analysis confirmed the formation of spherical nanoparticles with a uniform size distribution. The developed curcumin-loaded aquasomes exhibited promising characteristics, including enhanced solubility, controlled release, and high stability, making them a potential candidate for topical fungal treatment. These findings suggest that aquasome-based formulations can significantly improve the therapeutic efficacy of curcumin, offering a novel approach for the treatment of fungal skin infections.